Antibacterial and hemocompatibility potentials of nano-gold-cored alginate preparation against anaerobic bacteria from acne vulgaris - Hanan A. Abbas; Ali A. Taha; Ghassan M. Sulaiman; Amer Al Ali; Humood Al Shmrany; Haralambos Stamatis; Hamdoon A. Mohammed; Riaz A. Khan (Scientific Reports, 2024)
Abstract Acne is a prevalent dermatological disease, with high global incidence, and is a health menace. The current study aimed to isolate and characterize the anaerobic bacteria responsible for the condition. Causes of a total of 70 acne-based bacterium isolates obtained from patients of mild, moderate, and severe acne, 24 were Clostridium innocuum, 21 were Lactobacillus plantarum, 13 were Anaerococcus prevotii, and 12 were Peptoniphilus asaccharolyticus. Nearly 69% of males were suffering, while the rest were females at 31%. The 15–30 years old age group was the most affected. The gold/alginate nanoparticles’ nanopreparation (GANPs) produced from chloroauric acid and sodium alginate was an effective treatment against the acne conditions under the experimental conditions. The nanopreparation exhibited significant inhibitory activity against anaerobic bacterial isolates, with a minimum inhibitory concentration of 200 µg/ml for A. prevotii and P. asaccharolyticus, and 400 µg/ml for C. innocuum and L. plantarum. The in vitro efficacy of the GANPs on human blood parameters was also assessed. The concurrent results suggested potential antibacterial activity and hemocompatibility of the product, which has promise to be used as a successful antibacterial agent for acne.